The phenomenon of complete treatment refusal in patients with acute cerebrovascular accident (according to the LIS-2 registry) - Yu. V. Lukina; N. P. Kutishenko; A. V. Zagrebelny; M. L. Ginzburg; S. Yu. Martsevich; O. M. Drapkina (Рациональная фармакотерапия в кардиологии, 2024)
Aim. To describe and analyze a series of cases of absolute non-adherence to treatment (ANA), as well as to study the relationship of the phenomenon of refusal of treatment with long-term adverse outcomes in patients with acute cerebrovascular accident (ACVA), according to the LIS-2 registry (Lyubertsy Mortality Study 2).Material and methods. The study analyzed the results of two stages of prospective follow-up of patients with acute cerebrovascular accident included in the  LIS-2 registry (n=960). After 2.8 [2.1; 3.5] years, an examination, a survey, and an assessment of treatment adherence according to the original questionnaire were conducted in 370 patients. After 6.9 [6.1;7.7] years, the outcomes of these patients were evaluated. The survival analysis included death from all causes, nonfatal myocardial infarctions and repeated ACVA, and emergency hospitalization for cardiovascular diseases also. These are the components of the primary combined endpoint.Results. According to the results of the questionnaire, 23 (6,2%) patients replied that they did not take prescribed medications, i.e. they were absolutely not adherent to treatment. Absolutely non-adherent patients smoked more often (p=0.004), were less comorbid, and had statistically significant difference in hypertension and coronary heart disease (CHD) (p<0.001 and p=0.03, respectively). The most common reason for ANA was unwillingness to take medications for a long time (n=12, 52,2%), the second most common reason was fear of drugs side effects and harm to health during long-term treatment (n=5, 21.7%). The components of the primary combined endpoint were registered in 10 (43.5%) absolutely non-adherent patients and in 104 (30.0%) people of the rest of the group. There was a discrepancy in the Kaplan-M ayer survival curves for the groups of absolutely non-adherent and all other patients, which did not reach statistical significance (p=0.12), as well as an increased risk of adverse long-term outcomes (hazard ratio, HR) in patients who completely refused treatment: HR=1.68, 95% confidence interval (CI) 0.87-3.21, p=0.12 (univariate Cox analysis). According to the results of multivariate Cox regression analysis, the predictors significantly associated with an increase in the risk of endpoints were ANA (HR=2.66, 95% CI 1.06;6.68, p=0.037); presence of coronary heart disease (HR=2.18, 95% CI 1.13;4.24, p=0.021); increase in age for each year (HR=1.08, 95%CI 1.04;1.12, p<0.0001).Conclusion. The phenomenon of complete treatment refusal or ANA was noted in 6% of cases in patients with ACVA. Its leading cause was the reluctance of patients to take medications for a long time. In patients with ACVA it has been shown that the presence of CHD and complete refusal of recommended treatment increases the risk of adverse long-term outcomes by more than two times.